Association of ultra‐rare coding variants with genetic generalized epilepsy: A case–control whole exome sequencing study. Issue 3 (15th January 2022) - Koko, Mahmoud; Motelow, Joshua E.; Stanley, Kate E.; Bobbili, Dheeraj R.; Dhindsa, Ryan S.; May, Patrick; ,; ,; ,; ,; ,
Abstract: Objective: We aimed to identify genes associated with genetic generalized epilepsy (GGE) by combining large cohorts enriched with individuals with a positive family history. Secondarily, we set out to compare the association of genes independently with familial and sporadic GGE. Methods: We performed a case–control whole exome sequencing study in unrelated individuals of European descent diagnosed with GGE (previously recruited and sequenced through multiple international collaborations) and ancestry‐matched controls. The association of ultra‐rare variants (URVs; in 18 834 protein‐coding genes) with epilepsy was examined in 1928 individuals with GGE (vs. 8578 controls), then separately in 945 individuals with familial GGE (vs. 8626 controls), and finally in 1005 individuals with sporadic GGE (vs. 8621 controls). We additionally examined the association of URVs with familial and sporadic GGE in two gene sets important for inhibitory signaling (19 genes encoding γ‐aminobutyric acid type A [GABAA ] receptors, 113 genes representing the GABAergic pathway). Results: GABRG2 was associated with GGE ( p  = 1.8 × 10 −5 ), approaching study‐wide significance in familial GGE ( p  = 3.0 × 10 −6 ), whereas no gene approached a significant association with sporadic GGE. Deleterious URVs in the most intolerant subgenic regions in genes encoding GABAA receptors were associated with familial GGE (odds ratio [OR] = 3.9, 95% confidence interval [CI] = 1.9–7.8, false discovery rate [FDR]‐adjusted p  = .0024), whereas their association with sporadic GGE had marginally lower odds (OR = 3.1, 95% CI = 1.3–6.7, FDR‐adjusted p  = .022). URVs in GABAergic pathway genes were associated with familial GGE (OR = 1.8, 95% CI = 1.3–2.5, FDR‐adjusted p  = .0024) but not with sporadic GGE (OR = 1.3, 95% CI = .9–1.9, FDR‐adjusted p  = .19). Significance: URVs in GABRG2 are likely an important risk factor for familial GGE. The association of gene sets of GABAergic signaling with familial GGE is more prominent than with sporadic GGE.